SEPARATION AND ELEMENTATION OF DIMER STILBENOID STRUCTURE OF VATICA LIGHT STEEL UMBONATA BURCK (DIPTEROCARPACEAE) - Sri Atun (Jurnal Penelitian Saintek, 2007)
Three oligostilbenoid, namely (-)-ampelopsin F (1), laevifonol (2), ande-viniferin (3) had been isolated and elucidated these structure from the stem bark of  Vatica umbonata Burck (Dipterocarpaceae). The structure of three compounds were elucidated based on physical and spectroscopic data UV,JR,  IH and HCNMR, HMBC, HMQC, COSY, andNOESY.